Nomenclatural clarifications for names in Boschniakia, Kopsiopsis and Xylanche (Orobanchaceae) - Yu, Wen-Bin (Phytotaxa, 2013)
Phylogenetic evidence agrees with splitting Boschniakia C. A. Meyer sensu lato into three genera, Boschniakia, Kopsiopsis and Xylanche. In this study, we clarified some nomenclatural confusion concerning these three genera. The authorship of both Boschniakia and B. glabra is ascribed to C. A. Meyer, not C. A. Meyer ex Bongard or Bongard. Kopsiopsis hookeri (Walp.) Govaerts is the correct replacement name for the illegitimate name Orobanche tuberosa Hook. (1834), non Vell. (1829). Both Xylanche and X. himalaica were simultaneously validated in 1890.